Exploring Childhood Traumaand Coping Mechanisms Through Ferenczi’s Trauma Theory (Journal of Asian Development Studies, 2024)
This paper aims to achieve objectives to deepen the understanding of the psychological effects of childhood trauma, explore practical therapeutic approaches for addressing trauma, and provide insights into coping mechanisms. The significance of this research lies in its potential to offer strategies for recognizing and healing traumatic experiences in therapeutic settings. Grounded in Ferenczi’s trauma theory, this study analyzes the traumatic experiences of the protagonist in Pelzer's novel A Child Called 'It' (1995). By examining the protagonist's use of Ferenczi’s concept of “identification with the aggressor” and other coping techniques, the findings reveal the complex dynamics of trauma and its long-term consequences, highlighting the importance of therapeutic interventions in mitigating these effects.